Procalcitonin-guided algorithm to reduce length of antibiotic therapy in patients with severe sepsis and septic shock - Hohn, Andreas; Schroeder, Stefan; Gehrt, Anna; Bernhardt, Kathrin; Bein, Berthold; Wegscheider, Karl; Hochreiter, Marcel (BMC infectious diseases, 2013)
Procalcitonin (PCT)-protocols to guide antibiotic treatment in severe infections are known to be effective. But less is known about the long-term effects of such protocols on antibiotic consumption under real life conditions. This retrospective study analyses the effects on antibiotic use in patients with severe sepsis and septic shock after implementation of a PCT-protocol.
Gesehen am 17.08.2021